Urgensi Pembubuhan Meterai Pada Salinan Akta Sebagai Alat Bukti Berdasarkan Undang-Undang Nomor 10 Tahun 2020 - Andra Tanady; Elita Rahmi; Fauzy Syam (Universitas Batanghari Jambi, 2022)
Stamps in documents of a civil nature are very important for legal certainty in fulfilling evidence to be submitted to court. Therefore, stamp duty is very important in terms of proof in court so that in the use of stamp duty there are of course legal rules that regulate it. Even though there are legal rules that regulate it, often the Land Deed Making Officer violates the applicable legal rules. The problem to be studied is the regulation of the use of stamp duty on the copy of the deed of the Land Deed Official and the validity of the copy of the deed of the Land Deed Maker who uses stamp duty as evidence in court. The research method used is normative juridical so that the research is descriptive and the data source comes from secondary data, then this study uses a legal approach and a conceptual approach and analyzes the data using qualitative analysis. As for the results of the research, namely the regulation of the use of stamp duty on the copy of the deed of the Land Deed Official is regulated in Law Number 13 of 1985 concerning Stamp Duty, Draft Law of 2016, Law Number 10 of 2020 concerning Stamp Duty and the validity of the copy. Land Deed Officials who use stamps as evidence in court are regulated in Law Number 10 of 2020 concerning Stamp Duty that must put stamps on the signatures of Land Deed Making Officials so that they have legal force and fulfill legal certainty in order to be used as evidence. in the court.